Transforming Healthcare in Saudi Arabia through Strategic Planning and Innovation - Fahad Alqusumi (International Journal of Integrated Science and Technology, 2024)
The healthcare sector in Saudi Arabia is undergoing a significant transformation as part of the Vision 2030 initiative, with a focus on strategic planning and innovation. This study aims to provide an in-depth analysis of the healthcare transformation in the country since the inception of Vision 2030, highlighting key challenges and outlining steps taken to revolutionize health systems. The scoping literature review encompassing both published and unpublished sources was conducted, utilizing various databases with specific keywords related to Saudi healthcare, healthcare transformation, Vision 2030, Public-Private Partnerships, and privatization. Additionally, data from government reports, policies, strategy documents, and press releases were incorporated. The future of healthcare in Saudi Arabia hinges on achieving universal coverage while managing costs. Thereby, the national transformation program has implemented strategic measures to bolster the private healthcare sector, including the establishment of health clusters and the enactment of legislation such as the Private Sector Participation Law. Despite legislative advancements facilitating the transformation process, challenges persist, necessitating further research and caution. Most importantly, the role of innovation and technology in healthcare transformation is multifaceted and crucial for achieving various goals, including improving patient outcomes, enhancing efficiency, reducing costs, and increasing accessibility.